PENGUATAN NILAI-NILAI AGAMA DALAM KEHIDUPAN BERKELUARGA SEBAGAI UPAYA MENCEGAH DAN MENANGGULANGI KEKERASAN DALAM RUMAH TANGGA - Milo Nono, Anna Maria; Senda, Siprianus Soleman; Boe, Maria Roswita (STIPAS Keuskupan Agung Kupang, 2025)
Domestic violence is often triggered by a lack of communication, role inequality, and the weak application of religious values ​​within the family. Regarding the lack of application of religious values ​​within the family, the phenomenon of domestic violence demonstrates a gap between religious values ​​held and their practical application in domestic life. This study focuses on the weak application of religious values ​​in family life. This study uses a literature review method, utilizing written sources such as books, journals, and other documents as primary data to analyze the causes and prevention of domestic violence, particularly regarding the aspects of religious values ​​held and their application in domestic life. The purpose of this study is to identify solutions to prevent domestic violence by strengthening religious values ​​within the family. The results show that the application of religious values ​​such as love, justice, forgiveness, solidarity, kindness, truth, freedom, sincerity, and respect plays a crucial role in creating harmonious families and preventing domestic violence.